PEMANFAATAN FITOBIOTIK BERBASIS DAUN SIRIH (Piper betle linn) PADA AIR MINUM TERHADAP KONSUMSI DAN PERTAMBAHAN BOBOT BADAN (PBB) TERNAK AYAM KAMPUNG - Kustyorini, Tri Ida Wahyu; Brihandhono, Ari; Supardi, Hilarius (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aimed to evaluate the effect of betel leaf (Piper betle Linn)-based phytobiotics in drinking water on feed consumption and body weight gain (BWG) in native chickens, using two-month-old female chickens with an average initial weight of 1 kg in a completely randomized design (CRD). The treatments consisted of P0 (control, no betel leaf powder), P1 (2% betel leaf powder), and P2 (2.5% betel leaf powder), each replicated three times. Data on feed intake and BWG were analyzed using ANOVA, followed by the Least Significant Difference (LSD) test for significant results. The findings revealed that betel leaf phytobiotics had a highly significant effect (P 0.01) on feed consumption and a significant effect (P 0.05) on BWG, with P1 yielding the highest feed intake (133.67 g/bird/day) and P2 producing the highest BWG (12.22 g/bird/day). In conclusion, supplementing drinking water with 2.5% betel leaf powder optimized weight gain, while 2% supplementation maximized feed consumption, indicating that betel leaf phytobiotics can enhance native chicken growth performance, with dosage adjustments based on targeted outcomes.